Otopathogenic Pseudomonas aeruginosa Enters and Survives Inside Macrophages - Mittal, Rahul; Lisi, Christopher V.; Kumari, Hansi; Grati, M’hamed; Blackwelder, Patricia; Yan, Denise; Jain, Chaitanya; Mathee, Kalai; Weckwerth, Paulo H.; Liu, Xue Z. (Frontiers in Microbiology, 2016)
Otitis media (OM) is a broad term describing a group of infectious and inflammatory disorders of the middle ear. Despite antibiotic therapy, acute OM can progress to chronic suppurative otitis media (CSOM) characterized by ear drum perforation and purulent discharge. Pseudomonas aeruginosa is the most common pathogen associated with CSOM. Although, macrophages play an important role in innate immune responses but their role in the pathogenesis of P. aeruginosa-induced CSOM is not known. The objective of this study is to examine the interaction of P. aeruginosa with primary macrophages. We observed that P. aeruginosa enters and multiplies inside human and mouse primary macrophages. This bacterial entry in macrophages requires both microtubule and actin dependent processes. Transmission electron microscopy demonstrated that P. aeruginosa was present in membrane bound vesicles inside macrophages. Interestingly, deletion of oprF expression in P. aeruginosa abrogates its ability to survive inside macrophages. Our results suggest that otopathogenic P. aeruginosa entry and survival inside macrophages is OprF-dependent. The survival of bacteria inside macrophages will lead to evasion of killing and this lack of pathogen clearance by phagocytes contributes to the persistence of infection in CSOM. Understanding host–pathogen interaction will provide novel avenues to design effective treatment modalities against OM.